Design of rules for data intellectual property protection - FAN Li (大数据)
Through a study of a large number of intellectual property department laws, starting from the general principles and rules of intellectual property, the fitness of the concept of data intellectual property is demonstrated, and the differences between data intellectual property and concepts such as data property, data products, and data intellectual property construction schemes are clarified. Analyze the relationship between data intellectual property and the separation of data rights, the applicability of the data intellectual property system from the perspective of encouraging data circulation and usage, and clarify the rights of data intellectual property holders. Based on the development of the intellectual property system and case studies, propose understanding, guiding principles for registration, ideas for registration review, and specific examination standards for the elements of “obtaining data by laws and regulations, processing according to certain rules, and having practical value, intellectual achievement attribute, data set”, as well as substantive elements that data intellectual property should possess. Based on this, demonstrate the role of registration certificates and the criteria for determining the attributes of intellectual property.